Rancang Bangun Sistem Informasi Manajemen Angka Kredit Tenaga Kesehatan (SIMAK NAKES) Pada Dinas Kesehatan Kota Surakarta Berbasis Web - Setiawan, Yudi; Khusnuliawati, Hardika; Hari Saputro Al Haris, Firdhaus (UNIB Press, 2024)
The Surakarta Health Service oversees work units that have health functional positions. As one of the requirements for promotion and position, employees must create a credit point. However, the management process for determining credit points by the Surakarta Health Service is still manual using microsoft word and microsoft excel. It causes a long process, difficulty in finding information, and the risk of data loss. The research aims to design a web-based information system that will optimize the management of credit scoring for health workers at the Surakarta Health Service. The system development method used the waterfall method. System design used (UML) Unified Modeling Language. The system testing method used black-box testing and questionnaire testing. This research produces a website-based system at the Surakarta Health Service which has three actors, namely admin, UPT admin and users who have different access rights. The results of system testing using the black-box testing method show that the system is running well. The results of questionnaire testing using a Likert Scale shows that an average of 54.14% strongly agree with the use of the system, appearance, language, information, according to applicable guidelines, up to date, system performance, and system usefulness. Meanwhile, 46.25% agree that data management and information could be trusted. Keywords: Credit Point, Surakarta Health Service, Functional Position, Simak Nakes, Health Workers